PERANCANGAN METODE PERAMALAN PERMINTAAN DAN PERBAIKAN KEBIJAKAN PRODUKSI DI PT SOLAS LANGGENG SEJAHTERA - Pratama, Derbyfitri
PT Solas Langgeng Sejahtera is a company that operates in the pharmaceutical sector and produces various types of medicines, supplements, multivitamins, and cosmetics. Since the pandemic of Covid-19, product demand has become unstable. According to the company’s historical data, there was a 17% decrease in demand for ethical products in 2020, while demand increased by 12% in 2021. PT Solas Langgeng Sejahtera is currently experiencing difficulties due to an increase in the number of pending order each year. The number of pending orders increased by 249% in 2021. The company has not been able to predict demand, so the amount of product fulfillments to customers is also often delayed due to stockouts. Currently, the company uses a Simple Moving Average method with N=3 to predict demand for all product, and the average error value is obtained at 110% using Mean Absolute Percentage Error (MAPE) method. This research will design a demand forecasting method by testing five types of methods, including Simple Moving Average, Single Exponential Smoothing, Double Exponential Smoothing, Linear Regression, dan Triple Exponential Smoothing. This research will also design a production policy that is able to minimize total cost by considering the ratio and minimum stock. The result show that each product uses different forecasting methods according to past demand patterns. Using different forecasting methods for each product can reduce errors by 41,62%. Meanwhile, the production policy us being improved by changing the minimum stock value using the average demand to reduce the number of pending orders and total cost. The change in minimum stock resulted in an 8,87% decrease in the number of pending orders and a 2,15% decrease total costs.